2017
DOI: 10.3389/fimmu.2017.01306
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin Fragment 39-272 Promotes B16 Melanoma Malignancy through Myeloid-Derived Suppressor Cells In Vivo

Abstract: Calreticulin (CRT), a multifunctional Ca2+-binding glycoprotein mainly located in the endoplasmic reticulum, is a tumor-associated antigen that has been shown to play protective roles in angiogenesis suppression and anti-tumor immunity. We previously reported that soluble CRT (sCRT) was functionally similar to heat shock proteins or damage-associated molecular patterns in terms of ability to activate myeloid cells and elicit strong inflammatory cytokine production. In the present study, B16 melanoma cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Based on the combined results obtained by these experiments, we conclude that extracellular CALR is indeed immunosuppressive. This immunosuppression may also involve shifts in the composition of immune subpopulations (such an increase in MDSC) when CALR becomes elevated at the systemic level, as previously reported (He et al, 2017). At the conceptual level, the aforementioned results support the general notion that oncogenesis must be facilitated by the simultaneous occurrence of two processes, namely (1) the activation of cell-autonomous oncogenic drivers (and the inactivation of oncosuppressors) to create malignant cells and (2) the escape from immunosurveillance by ''hiding'' from the immune system or by active immunosuppression.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Based on the combined results obtained by these experiments, we conclude that extracellular CALR is indeed immunosuppressive. This immunosuppression may also involve shifts in the composition of immune subpopulations (such an increase in MDSC) when CALR becomes elevated at the systemic level, as previously reported (He et al, 2017). At the conceptual level, the aforementioned results support the general notion that oncogenesis must be facilitated by the simultaneous occurrence of two processes, namely (1) the activation of cell-autonomous oncogenic drivers (and the inactivation of oncosuppressors) to create malignant cells and (2) the escape from immunosurveillance by ''hiding'' from the immune system or by active immunosuppression.…”
Section: Discussionsupporting
confidence: 53%
“…CALR can be digested by proteases such as neutrophil elastase to generate a factor called vasostatin that inhibits angiogenesis (Mans et al, 2012). The systemic injection of CALR fragments into mice can also stimulate the expansion of myeloid-derived suppressor cells (MDSC) (He et al, 2017) or that of immunosuppressive B cells (Hong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical relevance of this process is supported by the fact that CALR exposure on cancer cells correlates not only with eIF2α phosphorylation but also with prognostically favourable anticancer immune responses 65,66 . Of note, dying cancer cells can also release soluble CALR, which limits the ability of macrophages to present phagocytosed antigens (as a consequence of MHC class II downregulation) 67 and favours the accumulation of myeloidderived suppressor cells (MDSCs) 68 , hence potentially promoting tumour progression. Thus, the net microenvironmental effect of UPR ER -driven CALR signalling may depend on the balance between the surface-bound and soluble variants of the molecule.…”
Section: Box 1 | the Dna Damage Response At A Glancementioning
confidence: 99%
“…MPL induces the accumulation of MDSCs both in vitro and in vivo by inhibiting DC development from myeloid cells ( 57 ). In addition, in a melanoma mouse model, soluble calreticulin (sCRT39-272) was demonstrated to promote the migration and survival of tumor-derived MDSCs via interactions with TLR4 ( 52 ). Notably, Li et al ( 58 ) demonstrated that exogenous S100A4 upregulates TLR4 receptor expression on MSC2 cells and protects MDSCs from apoptosis via the TLR4/extracellular regulated protein kinases (ERK)1/2 signaling axis, both in vitro and in vivo .…”
Section: Pro-tumorigenic Effects Of Mdscs Induced By Tlr Signalingmentioning
confidence: 99%
“…De Veirman et al ( 54 ) demonstrated that S100A9 acts as a chemokine for multiple myeloma (MM) cells and induces MDSCs to express and secrete inflammatory and promyeloma cytokines, including TNF-α, IL-6 and IL-10. In addition, He et al ( 52 ) demonstrated that TLR4 signaling inhibits MDSC differentiation into DCs and promotes their functional maturation, and the chemotactic migration of MDSCs by initiating the expression of S100A8 and S100A9. Recent studies on colorectal cancer ( 53 ) and MM ( 54 ) have demonstrated that S100A9 promotes the expression levels of Arg1, iNOS and IL-10, and ROS production in MDSCs via TLR4-NF-κB signaling cascades, thereby inhibiting CD8 + T cell activity and promoting tumor progression ( 53 ).…”
Section: Pro-tumorigenic Effects Of Mdscs Induced By Tlr Signalingmentioning
confidence: 99%